Keamanan Sepeda Motor menggunakan GPS dan LCD Nextion berbasis mikrokontroler - Rio Rizky Sugiarto; Muhammad Aria Rajasa (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2018)
Abstract - Motor vehicles at this time have been very much in our environment. Motorbike loss often occurs due to carelessness of the owner of the motor vehicle itself and the environment that is not safe. Some of the things that often happen when heating a motorcycle outside the house and left behind just light up. The security system on the motorbike is now good, however, there is still a lot of theft, therefore, a motorcycle security system is created. using pins and fingerprints, with hope, can minimize theft of motorcycle vehicles. The security system is made, there is also a Global Position System (GPS), so as to facilitate users to monitor motorcycle vehicles. With the results of the experiments carried out, using a pin and fingerprint security system that is based on a microcontroller or also commonly referred to as Arduino Mega, which acts as a security system on a motorcycle, can improve better safety on a deep-seated motorcycle the condition is being parked. The design of the security system implanted on this motorcycle is a form of application in the use of a microcontroller system that can respond to inputs and outputs including in Keypad, Liquit Crystal Display (LCD) and fingerprint. The results achieved are making a pin and fingerprint security system that is interconnected with Arduino Mega, with the help of GPS as tracking. With the creation of this security tool, it is expected to be able to minimize the crime of motorcycle thieves that always exist in the present, by making these tools will create a motorcycle security tool which is expected to minimize the theft of motorcycle vehicles and also minimize material losses to motorcycle owners. In addition to minimizing the level of theft of motorbike vehicles, it is expected to make people more calm.Keyword : The motor security system uses fingerprint sensor, GPS, LCD Nextion